The role of the Qur'an in deriving Shariah rulings for financial transactions - Kamaruszaman, Muhammad Hazim; Rohadi, Muhammad Arif Izzuddin; Mazlan, Muhammad Hasif; Ahmad Nasir, Ahwaz (2025)
The Qur'an plays a very important role as a source of law in Islam. It not only serves as a spiritual guide for Muslims, but also as a fundamental reference in various aspects of life, including transactions, which cover economic and social interactions. By studying the Qur'an, one can obtain legal principles that ensure justice and prosperity in society. The laws contained in the Quran are based on the revelations received by the Prophet Muhammad (peace be upon him) and form a framework for understanding and applying Sharia law among Muslim communities. (Marwa, 2021) The uniqueness of the Qur'an lies in its origins and the methods of interpretation prevalent among Muslims. The Qur'an functions not only as a sacred text, but also as a guide for life. For example, in the context of transactions, various laws based on justice, honesty and social responsibility are clearly defined in the Qur'an. The mechanism of legal sustainability mechanism used to interpret and apply it in various current situations, ensuring its relevance in modern life. (Abubakar, 2023). In this study, the deductive approach will focus on understanding the apparent/detailed pronunciation), the general division and discourse, as well as the specialisation of Nas through the concepts of mutlak al-muqyad and amar nahi. Each method of interpreting the verses of transactions will be applied in a systematic manner, followed by examples from practical laws such as the prohibition of usury, the obligation to record debts, and the principle of analogy. Finally, the conclusion will highlight the contribution of the Qur'an to the formation of a just and ethical Islamic economic framework in the current context.